DAMPAK KEBIJAKAN PEMBANGUNAN PERUMAHAN (STUDI DI DESA SEA KECAMATAN PINELENG KABUPATEN MINAHASA) - KALAMPUNG, GERRY ALFERO; LALOMA, ALDEN; KOLONDAM, HELLY (JURNAL ADMINISTRASI PUBLIK, 2020)
The purpose of this study was to determine the impact of public housing development policies in the Sea Village of Minahasa Regency. This study uses a descriptive-cumulative approach. Research informants were the village head, housing residents, and community leaders / residents of the Sea Village. The data analysis technique used is an interactive model analysis of Miles and Hubernann. Research Results Show: (1) Housing development policies in Sea Village have a positive impact on public matters and on the target group's policy community, which is to help people who do not yet have a home to get housing loans with affordable installments, and in locations that are accessible comfortable and safe. Housing development does not have the expected impact of disturbing security and comfort in society. The unexpected impact is mainly the reduction in agricultural land and community forestry. (2) Housing development policies have a positive impact on economic and social conditions in Sea Village, namely increasing people's income and increasing the progress of social life such as education, social and community social activities, and development participation. (3) Housing development policies have a positive impact on current conditions in Sea Village, namely increasing the progress and development of the village and community now and in the future. (4) Housing development policies in Sea Village do not have an impact on the direct and indirect costs that must be borne by the community as a result of the housing construction. Keywords: Impact of Policy, Housing Development